Milk Fat Globule Membrane Attenuates Acute Colitis and Secondary Liver Injury by Improving the Mucus Barrier and Regulating the Gut Microbiota - Wu, Zhenhua; Liu, Xiaoyi; Huang, Shimeng; Li, Tiantian; Zhang, Xiangyu; Pang, Jiaman; Zhao, Junying; Chen, Lijun; Zhang, Bing; Wang, Junjun; Han, Dandan (Frontiers in Immunology, 2022)
Objective Inflammatory bowel disease (IBD) is often along with extraintestinal manifestations including hepatic injury. Milk fat globule membrane (MFGM) is an active substance with potential anti-inflammation activity. However, its alleviated effect and mechanisms in IBD as well as the IBD-induced secondary liver injury are still unclear. Methods C57BL/6J mice were administered with 21-day oral gavage of MFGM, followed by 7-day drinking water with 4% dextran sulfate sodium (DSS). Disease activity index (DAI), histological features, and cytokines of colon and liver were evaluated. Then RNA-seq of colon and liver were conducted. The gut microbiota was assessed by analyzing 16S rRNA gene sequences, and finally the integrity and function of mucus barrier were evaluated by alcian blue staining, real-time quantitative PCR and ELISA. Results Prophylactic MFGM treatment was effectively against colitis, to include effects in body weight loss, DAI score, colonic length, intestinal pathology, and histological score. Additionally, prophylactic MFGM decreased the levels of interleukin (IL)-1β, IL-6 and myeloperoxidase (MPO) in colonic tissue, while increased the IL-10 level. Moreover, the genes expressions of MUC2, MUC4, Reg3b and Reg3g associated with production of molecular mediator of immune response, membrane invagination, and response to protozoan were strikingly up-regulated when administered with MFGM. On the other hand, the beneficial effects of MFGM were related to the enriched abundance of genera such as Faccalibacumum and Roseburia in feces samples. Consistently, administration of MFGM was also found to alleviate DSS-induced hepatic injury. Furthermore, the glutathione transferase activity pathway was enriched in the liver of MFGM-treated mice after DSS administration. Mechanistically, prophylactic MFGM enhanced mucosal barrier by increasing the gene levels of Reg3b and Reg3g. Meanwhile, the alleviation of MFGM on liver injury was dependent on the reduced hepatic oxidative stress. Conclusions MFGM attenuated colitis and hepatic injury by maintaining the mucosal barrier and bacterial community while inhibiting oxidative stress, which might be an effective therapy of hepatic injury secondary to IBD.